762 Medical management of organic psychomotor agitation and neuroreabilitation after revascularised vertebrobasilar stroke (Balneo and PRM Research Journal, 2025)
(1) Background: Psychomotor agitation is a behavioral and emotional symptom frequently seen in dementia patients. Vascular dementia has few options for treating non-cognitive symptoms such as agitation and psychotic symptoms. (2) Methods: We present the case of a 71-year-old male who presented in the revascularisation window for confusional syndrome and tetrameric ataxia. The examination revealed: psychomotor agitation, dyscromatopsia, self-disorientation, temporal and spatial disorientation, complex visual hallucinations with Capgras syndrome, facial agnosia, and akinetopsia. (3) Results: Brain CT revealed top of the basilar artery thrombosis which was treated with mechanical thrombectomy and intraarterial thrombosis. Brain imaging revealed constitutive lesions in the occipital lobe, parahippocampal, the lingual gyrus, in the paramedian pontine level, and a cerebellar lesion. The patient developed strategic infarct dementia with severe psychomotor agitation. As a therapeutic approach, the heroic combination that diminished the agitation was: Olanzapine and Levomepromazine (two sedative neuroleptics), Valproate (thymostabiliser), and Diazepam. (4) Conclusions: We emphasize the need for heroic treatment options for severe psychomotor agitation and psychotic agitation in patients with cardiovascular risks such as stroke. In this case, we present our beneficial results with Olanzapine and Levomepromazine. We highlight the need for extensive treatment guidelines for severe cases of psychomotor agitation.